To Evaluate the Safety and Efficacy of Autologous Nonspecific Activated T-Cells Therapy For 7,12-Dimethylbenz[A]Anthracene (DMBA) Induced Breast Cancer in Female Rats-A Supportive Care - Sah, Saroj Kumar; Jha, Deepak Kumar; Fathima, Mehdi (Indian Journal of Pharmaceutical Education and Research)
Background and objectives: Breast cancer persist a core cause of mortality in women, and current treatments like Tamoxifen often fail to address immune suppression within the tumor microenvironment. Autologous nonspecific activated T-cell therapy, either alone or combined with Tamoxifen, has shown promise in enhancing immune responses and overcoming these barriers in treating breast cancer induced by DMBA in female rats. Materials and Methods: The study involved administering DMBA to induce breast cancer in female rats, grouped into following groups; normal control, disease control, Tamoxifen alone, and three T-cell therapy groups; one combination with tamoxifen. T-cell therapy involved isolation, culture, and activation of MNCs from rats, administered intravenously and intra-tumor in combination with Tamoxifen. Tumor growth, immune markers, cytokines, and inflammatory markers were monitored. Key Observations: T-cell therapy showed promising tolerance and efficacy in treating aggressive tumor progression. While tamoxifen partially reduced tumor size and inflammation, its immune impact was minimal. Intravenous T-cell therapy yielded limited results, whereas intratumor T-cell administration led to significant tumor regression and immune enhancement. Combined intratumor T-cell therapy with tamoxifen achieved near-complete tumor regression, increased CD3, CD4, CD8, lymphocyte counts, elevated INF-γ, and reduced IL-6. Histology confirmed improved tissue regeneration, supporting the potential of combined immune and conventional therapies. Conclusion: The study found that the combination of intratumor T-cell administration and tamoxifen effectively treated DMBA-induced breast cancer, leading to near-complete tumor regression, elevated interferon-gamma levels, and reduced IL-6. The therapy also promoted tumor suppression and immune system recovery, resulting in increased lymphocyte counts and CD4+ T-Cell Subsets.
Keywords: Breast Cancer; Cytokine; DMBA; Mononucleated cells; T cell therapy; Tamoxifen; Tumor Regression.